A Love Song for All of Us?: Macklemore's "Same Love" and the Myth of Black Homophobia. Issue 4 (November 2018) - KEHRER, LAURON
Abstract: According to the New York Times, white rapper Macklemore and his DJ partner Ryan Lewis's "Same Love" was "the first song to explicitly embrace and promote gay marriage that has made it into the Top 40." 1 In 2013, as the Supreme Court of the United States prepared to rule on challenges to the Federal Defense of Marriage Act and California's Proposition 8, which banned same-sex marriage, the track quickly climbed the charts and became a nationally recognized anthem for marriage equality. Despite this generally positive reception, however, the song does not reflect all queer-identified listeners. Macklemore raps, "If I were gay, I would think hip hop hates me, " an assertion that positions black communities as a significant threat to (white) LGBTQ rights. Much like the backlash against black voters following the 2008 passing of Proposition 8, this claim relies on an invented black pathology that locates homophobia in black American culture specifically rather than American culture at large. This article offers a close reading and contextualization of "Same Love" and demonstrates that, rather than combating homophobia in hip hop, Macklemore's lyrical claims actually bolster his strategic performance as a socially and politically aware white rapper, while erasing queer and trans hip hop artists of color from the discourse.